2016
DOI: 10.7863/ultra.15.11087
|View full text |Cite
|
Sign up to set email alerts
|

Epipericardial Fat Necrosis

Abstract: Epipericardial fat necrosis is a rare cause of chest pain. It presents as pleuritic pain in an otherwise healthy patient. Computed tomography has proved to be the most effective diagnostic imaging technique because of its ability to reveal typical alterations in the cardiophrenic space. As far as we know, sonographic findings concerning this entity have not been reported in the literature. We report 4 cases admitted to our institutional emergency department with chest pain. Among other tests, chest wall sonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…Diaz et al reported sonograms of four cases, which showed an ovoid mass surrounded by a hypoechoic halo. The sonographic findings in epiploic appendagitis and lipo-necrosis of subcutaneous adipose tissue are similar to those seen in EFN [28,29]. EFN may display increased uptake on gallium Ga-67 scintigraphy.…”
Section: Image Findingssupporting
confidence: 55%
“…Diaz et al reported sonograms of four cases, which showed an ovoid mass surrounded by a hypoechoic halo. The sonographic findings in epiploic appendagitis and lipo-necrosis of subcutaneous adipose tissue are similar to those seen in EFN [28,29]. EFN may display increased uptake on gallium Ga-67 scintigraphy.…”
Section: Image Findingssupporting
confidence: 55%
“…Chest wall sonography in the emergency setting of chest pain after ruling out myocardial infarction has been reported. 26 Here, the researchers found particular sonographic findings in 4 patients, consisting of hyperechoic nodules in the epipericardial fat surrounded by a hypoechoic halo and increased echogenicity of adjacent adipose tissue. Findings were consistent with EFN on CT and sonographically like other forms of fatty necrosis.…”
Section: Discussionmentioning
confidence: 83%
“…No age predilection is known to exist, but the typical patient has so far been characterized as middle-aged with presentation at 43 to 50 years. 3 , 4 , 11 , 14 , 16 The latest articles in our search (2016-2019) reported in sum slightly younger patients 2 , 9 , 10 , 22 , 23 , 25 , 26 , 28 , 29 resulting in a mean age of 39.4 years. Lately, reports of EFN in the paediatric population have also emerged.…”
Section: Discussionmentioning
confidence: 90%